Historical amnesia: a study into the causes of the disconnection between communities and their rock art sites at Chongoni Rock Art World Heritage Site - Chiumia, Chrissy Chimodzi (My University, 2013)
This study examines the history by which the local communities became separated from their ancestral heritage at Chongoni World Heritage Site in Malawi and then uses this knowledge to improve the management and conservation of rock art sites in the area. It demonstrates how various forces of the distant and immediate past came into play and systematically disconnected the Chewa communities around Chongoni area from their ancestral rock shelters once used by scores of generations for many important functions such as rock painting, rainmaking ceremonies and boys and girls initiation rituals. It shows that the separation of these communities from their heritage happened gradually in various episodes spread over the past 150 years. The key factors that directly or indirectly led to the separation included the early conquest of the Chewa communities by the Ngoni and other groups; conflicts with early Christian missionaries; heavy handed policies of the British colonial government; social and political failures of the post-independent state; the rise of multiparty politics, governance and human freedoms and others. Using local evidence, I build a case for each of the mentioned factors and shows how this community is still in danger of not only being completely separated from their ancestral heritage but also losing the remaining strands of their unique traditions. The study concludes by making recommendations for instituting participatory approaches in the management and conservation of Chongoni World Heritage Site.
Keywords: Art, Prehistoric - Malawi.; Rock paintings - Malawi.; Rites and ceremonies - Malawi.; Malawi - Antiquities.